2003
DOI: 10.1188/03.onf.575-581
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Handling Practices of Outpatient and Office-Based Oncology Nurses

Abstract: Safety concerns and potential adverse health effects associated with the occupational handling of chemotherapeutic agents have been reported. Historically, nurses' adherence to chemotherapy-handling guidelines has been poor. Results suggest that adherence is increasing; however, research is lacking regarding nurses' level of knowledge of and specific barriers to safe handling of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 9 publications
4
47
0
1
Order By: Relevance
“…The percent of respondents participating in a medical surveillance program (19%) was markedly lower than reported (46%, 47%) in previous surveys. (24,27) …”
Section: Discussionmentioning
confidence: 99%
“…The percent of respondents participating in a medical surveillance program (19%) was markedly lower than reported (46%, 47%) in previous surveys. (24,27) …”
Section: Discussionmentioning
confidence: 99%
“…The ability of the toothbrush to remove plaque is consistently better and more clinically useful than foam swabs. [8][9][10][11][12][13][14] Grap et al 5 found that toothbrushing was not routinely performed and that sponge toothettes were used more often than toothbrushes were used for patients receiving mechanical ventilation. Antimicrobial chlorhexidine gluconate has been tested as a potential strategy for preventing VAP in several studies.…”
mentioning
confidence: 99%
“…Antimicrobial chlorhexidine gluconate has been tested as a potential strategy for preventing VAP in several studies. [10][11][12][13][14] When our study was done, no published studies had demonstrated a definitive link between chlorhexidine use and decreased VAP rates for critically ill patients. Recent studies [15][16][17] show a reduction in VAP rates when chlorhexidine is used, but the role of chlorhexidine in preventing VAP in critically ill patients remains unclear.…”
mentioning
confidence: 99%
“…It is further suggested that the use of other equipment has improved, but remains under-compliant with OSHA guidelines. 73 Another recent study done in Israel examined the influence of the nurses' knowledge, attitudes and health beliefs on their behavior regarding safety measures. In general, nurses in this study did not fully comply with their facility's regulations for the safe handling of HD partly due to an education deficit.…”
Section: Practices Of Hcws Handling Hdsmentioning
confidence: 99%
“…[55][56][57][58][59][60][61][62][63][64][65][66][67] Findings from studies dating back to the 1980s are alarming given the knowledge offered by today's 20/20 hindsight regarding the risk these agents pose. In general, in that era when practice guidelines were first being developed and implemented, gloves were the most commonly used PPE, but even their use was comparatively low.…”
Section: Practices Of Hcws Handling Hdsmentioning
confidence: 99%